Acquisition of Traffic Related Language Through Contemporary Scientific and Technical Publications - Dušan Fabe (Promet - Traffic&Transportation, 1970)
Like teachers of subject related languages in general alsothe teachers of traffic related language are faced with the challengesof contemporary, technologically fast developing society.In modem information times students are much better informedthrough satellite TV; Internet and numerous publications.On the other hand, getting hold of all this information isno easy task for teachers. If they want to be interesting andmake students attend their classes, they must even be ahead oftime or at least be the first to pass on fresh information. Here aquestion arises about the current role of language textbooks intertiary education. Writing of a good textbook requires at least ayear or two, considering the time from its conception to publication.However, by that time it is no longer up-to-date. One ofthe solutions to the problem is presentation of current articlesfound by students in various contemporary scientific and technicalpublications. The present paper gives recommendations,based on long experience, how to acquire traffic-related languagewith such presentations in class.